Migration In Catalan (1975-2000). Reflections On The State Of The From The Social Sciences - Solana Solana, Miguel; Morén Alegret, Ricard; De Miguel Luken, Verónica; Pascual De Sans, Àngels (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
Migrations in Catalonia and researches carried out on them from the social sciences have experienced a series of changes during the last decades, while other features have remained almost unchanged. In this article some reflections based on materials that are focused on such issues and have appeared during the last twenty-five years are presented. Concretely, the main conclusions of a recent study signed by the authors and based, among other data basis, on a census including over one thousand works have been synthesised here. In an introductory section, the main aims of that research and its spatio-temporal definition are noted, along the key characteristics of the analysed data basis. Secondly, some considerations on the scope of the research on migrations in Catalonia is developed, including data on the university production, the number of articles found in academic journals, etc. In a third moment, some reflections on the timing and spatial scales of analysis are incorporated. In a fourth section, an analysis of the main topics studied in the items included in the data base is undertaken. Fifthly, several issues linked to migrations that have been so far scarcely researched and that would be interesting to study in the future are suggested in another section. Finally, other previous states-of-the-art on migrations in Catalonia and Spain that have been published during the last years are mentioned closing the article.